GSK-3β Inhibitor Alsterpaullone Attenuates MPP+-Induced Cell Damage in a c-Myc-Dependent Manner in SH-SY5Y Cells - Wang, Jiancai; Li, Yuqian; Gao, Li; Yan, Fengqi; Gao, Guodong; Li, Lihong (Frontiers in Cellular Neuroscience, 2018)
Mitochondrial dysfunction plays significant roles in the pathogenesis of Parkinson’s Disease (PD). The inactivation of c-Myc, a down-stream gene of Wnt/β-catenin signaling, may contribute to the mitochondria dysfunction. Inhibition of glycogen synthase kinase 3β (GSK-3β) with Alsterpaullone (Als) can activate the down-stream events of Wnt signaling. Here, we investigated the protective roles of Als against MPP+-induced cell apoptosis in SH-SY5Y cells.The data showed that Als effectively rescued c-Myc from the MPP+-induced decline via Wnt signaling. Furthermore, Als protected SH-SY5Y cells from the MPP+-induced mitochondrial fission and cell apoptosis. However, the protective roles of Als were lost under β-catenin-deficient conditions. These findings indicate that Als, a GSK-3β inhibitor, attenuated the MPP+-induced mitochondria-dependent apoptotic via up-regulation of the Wnt signaling.